2017
DOI: 10.22632/ccs-2017-251-89
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Mobile Learning with WhatsApp based on Media Richness

Abstract: With the proliferation of mobile devices, mobile learning has become a learning paradigm in education. The aim of this paper is to evaluate the media richness of various message delivery methods in mobile learning (m-learning) environment. This study evaluates media richness in respect to content timeliness, content richness, content accuracy and content adaptability in WhatsApp, Email, SMS, Twitter and BBM. One-way ANOVA analysis and Post hoc analysis show that: (i) SMS has better performance than WhatsApp, E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 22 publications
0
13
0
1
Order By: Relevance
“…Findings from the study indicate that participants can communicate and learn through WhatsApp wherever they may be. According to Boyinbode et al, (2017), confirm that due to the media richness of WhatsApp, it is more suitable for mobile learning. The following statistics from their study show social media applications that will best engender mobile learning are as follows: 65% for WhatsApp, 25% for Email, 10% for Twitter, and 10% for BBM.…”
Section: Discussionmentioning
confidence: 93%
“…Findings from the study indicate that participants can communicate and learn through WhatsApp wherever they may be. According to Boyinbode et al, (2017), confirm that due to the media richness of WhatsApp, it is more suitable for mobile learning. The following statistics from their study show social media applications that will best engender mobile learning are as follows: 65% for WhatsApp, 25% for Email, 10% for Twitter, and 10% for BBM.…”
Section: Discussionmentioning
confidence: 93%
“…There are plenty of features that make use of WhatsApp in HEIs more attractive as outlined by Kadam and Mhatre (2016), Boyinbode et al. (2017) and Bouhnik and Deshen (2014).…”
Section: The Whatsapp Messenger: Its Background Features and Usementioning
confidence: 99%
“…There are plenty of features that make use of WhatsApp in HEIs more attractive as outlined by Kadam and Mhatre (2016), Boyinbode et al (2017) and Bouhnik and Deshen (2014). One of the features is that WhatsApp has a capability of being customised to operate in various smartphone operating systems such as Android and can be accessed through most other smartphones regardless of the operating system or the type of the smartphone.…”
Section: The Whatsapp Messenger: Its Background Features and Usementioning
confidence: 99%
“…The final two features, media support and message latency, were more directly related to communication richness. Boyinbode et al (2017) reported similar findings when comparing WhatsApp, Twitter, Blackberry Messaging, SMS and email: they found that participants differentiated between the different tools based primarily on message latency while rating them roughly the same on media support.…”
Section: What Is It About Whatsapp?mentioning
confidence: 56%